(Shrinking) Civic Space in Nepal: Concerns Among Indigenous People's Organizations. Issue 2 (3rd May 2020) - Uprety, Uttam
Abstract: Nepali civil society organizations, particularly indigenous people's organizations, have been functional for many years. Despite representing nearly 40 per cent of the population, indigenous people in Nepal are witnessing increasing efforts by the government to shrink their civic space through restrictive legal measures. As a reaction, a section of civil society has initiated countering it through various advocacy activities. The exploratory study investigates how indigenous people's organizations (IPOs) understand their position within Nepali civil society, explores their concerns regarding the current regulatory changes, and contextualizes these relationships within a broader trend of shrinking civic space. Based on cases of four IPOs, the worldviews of these indigenous organizations are contrasted with more conventional CSOs in Nepal. Major differences include: (a) lack of customary practices in proposed Common Law, (b) limited voice and participation of indigenous people in public consultation processes, (c) lack of recognition of the specificities of IPOs, (d) overt formalization of CSOs in terms of registration, and (e) politicization of civil society that is detrimental to IPOs.